Quick survey for detection, identification and characterization of Acanthamoeba genotypes from some selected soil and water samples across Pakistan - Tania Tanveer; Abdul Hameed; Asma Gul; Abdul Matin (Annals of Agricultural and Environmental Medicine, 2015)
[i]Acanthamoeba[/i] is an opportunistic protozoan pathogen which is widely distributed in nature and plays a pivotal role in ecosystem. [i]Acanthamoeba[/i] species may cause blinding keratitis and fatal granulomatous encephalitis involving central nervous system. In this study, we investigated the presence of [i]Acanthamoeba[/i] in soil and water resources of Pakistan. Here, [i]Acanthamoeba[/i] were recovered on non-nutrient agar plate lawn with [i]E.[/i] [i]coli[/i] and identified by morphological characteristics of the cyst. Furthermore PCR was performed with genus-specific primers followed by direct sequencing of the PCR product for molecular identification. Overall our PCR and sequencing results confirmed pathogenic genotypes including T4 and T15 from both soil and water samples. This is our first report of [i]Acanthamoeba[/i] isolation from both soil and water resources of Pakistan which may serve as a potential treat to human health across the country.